A CFD simulation study on the effect of velocity and pressure distributions in wet gas metering using slotted orifice flow - Muhammad Syazuwan, Nordin (2015)
This paper presents the simulation studies on the effect of velocity and pressure distributions in wet gas metering of slotted orifice flow using Computational Fluid Dynamic (CFD) simulations with the Gambit 2.4.6 and Fluent 6.3.26 software. The effect of velocity and pressure distributions in wet gas metering using slotted orifice flow meter was clearly understand by fully developed a turbulent condition in the 1.6 in long horizontal pipe line equipped with slotted orifices having a 3 ratio of 0.40. Air mass flow rate and volume fraction were varied in the range from 0.33 kg/s to 0.80 kg/s and 0.90 to 1.00, respectively. Pressure was also varied in the range of 240000 - 360000 Pa. The slotted orifice results were also compared with the standard orifice with the same 3 ratio. Gambit 2.4.6 mesh generator was employed to perform all geometry generation and meshing. The relatively higher over-reading values obtained in this work was consistent with the results of that for a slotted orifice, a low P ratio was more sensitive to the liquid presence in the stream and hence was preferable for wet gas metering. Total mass flows for the wet gas get from the simulations were varied from the 0.3376 kg/s to 0.8000 kg/s. In conclusion, the numerical results indicate that pressure drop and static pressure recovery was better with the slotted orifice, and hence was preferable for wet gas metering. Moreover, with the rectangular slots, the static pressure recovery improves marginally as the aspect ratio increases. It was also found that the slotted orifice was more sensitive to wet gas flow compared to the standard orifice.